Risk‐based seismic design for collapse safety. (1st March 2016) - Sinković, Nuša Lazar; Brozovič, Marko; Dolšek, Matjaž
Summary: Risk‐based seismic design, as introduced in this paper, involves the use of different types of analysis in order to satisfy a risk‐based performance objective with a reasonable utilization rate and sufficient reliability. Differentiation of the reliability of design can be achieved by defining different design algorithms depending on the importance of a structure. In general, the proposed design is iterative, where the adjustment of a structure during iterations is the most challenging task. Rather than using automated design algorithms, an attempt has been made to introduce three simple guidelines for adjusting reinforced concrete frames in order to increase their strength and deformation capacity. It is shown that an engineer can design a reinforced concrete frame in a few iterations, for example, by adjusting the structure on the basis of pushover analysis and checking the final design by means of nonlinear dynamic analysis. A possible variant of the risk‐based design algorithm for the collapse safety of reinforced concrete frame buildings is proposed, and its application is demonstrated by means of an example of an eight‐storey reinforced concrete building. Four iterations were required in order to achieve the risk‐based performance objective with a reasonable utilization rate. Copyright © 2016 John Wiley & Sons, Ltd.